1988
DOI: 10.1103/physrevlett.60.1010
|View full text |Cite
|
Sign up to set email alerts
|

Polarization of molecular x-ray fluorescence

Abstract: Polarization of CI Kfi x-ray fluorescence following selective excitation of gaseous CH3CI with synchrotron radiation is reported. The degree of polarization of the fluorescence depends sensitively on the chosen incident excitation energy in the CI A^-edge region. Theoretical considerations indicate that the fluorescence-polarization measurements can provide directly absorption and emission anisotropics, molecular-orbital symmetries, and relative fluorescence transition strengths.PACS numbers: 33.20. Rm, 33.50.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 10 publications
3
18
0
Order By: Relevance
“…Although it is an accepted fact that without additional interactions, such as vibronic coupling, the symmetry must be restored for the exact electronic core hole state wave function, direct experimental evidence has been lacking to prove just that. The introduction of high-brightness synchrotron radiation sources has opened new possibilities to measure resonant core-electron spectra [5] and thereby reach conclusions on this issue by purely experimental means. Resonant x-ray emission provides such a possibility because the dipole character of the absorption and emission leads to simple selection rules also for the full scattering process [4].…”
mentioning
confidence: 99%
“…Although it is an accepted fact that without additional interactions, such as vibronic coupling, the symmetry must be restored for the exact electronic core hole state wave function, direct experimental evidence has been lacking to prove just that. The introduction of high-brightness synchrotron radiation sources has opened new possibilities to measure resonant core-electron spectra [5] and thereby reach conclusions on this issue by purely experimental means. Resonant x-ray emission provides such a possibility because the dipole character of the absorption and emission leads to simple selection rules also for the full scattering process [4].…”
mentioning
confidence: 99%
“…2,3 Polarization and anisotropy of x-ray emission can be used to study orbital components, bond directions, and molecular orbital symmetries. [4][5][6] Recently, molecular-field effects a) Author to whom correspondence should be addressed. Electronic mail: tatiana.marchenko@upmc.fr.…”
Section: Introductionmentioning
confidence: 99%
“…33 The second maximum at 2826.7 eV is attributed to transitions to Rydberg states of (1a 1 → np) symmetry converging to the threshold at 2828.4 eV, indicated by the vertical bar in Fig. 1.…”
Section: K α Emission Lines In Methyl Chloridementioning
confidence: 97%
“…It has been shown that polarized x-ray-emission spectroscopy allows direct determination of the symmetries of occupied/unoccupied valence molecular orbitals and the anisotropy in absorption and emission processes. 33,[42][43][44] Using the polarimeter capabilities of the ALS spectrometer, K α emission lines were recorded after resonant photoexcitation at the Cl 1s → 8a 1 resonance for ten different θ angles between incident ( e 1 ) and emitted ( e 2 ) polarization vectors. The experimental spin-orbit ratio were measured from a least-squares fit procedure of the K α emission lines by two Voigt profiles assuming identical emission profiles for the SO doublet 2p 3/2 and 2p 1/2 .…”
Section: B Linear Dichroism In the Polarization Dependence Of K α Emmentioning
confidence: 99%